THE RELATIONSHIP BETWEEN WORK STRESS AND MENTAL HEALTH IN CV EMPLOYEES. MASTERPIECE PRESTASI - Leonardo Chandra; Jaron VIncent; Jesslyn Noreen; Haposan Lumbantoruan (SOSIOEDUKASI, 2025)
Work stress that is not managed properly has the potential to affect employees' mental health and has an impact on decreased work productivity to extreme termination of employment. This study aims to analyze the relationship between work stress and the mental health of CV employees. Masterpiece of Prestasindo. The approach used is a quantitative research with a simple regression analysis technique using SPSS version 27. The study population consisted of 110 employees, and through the Isaac & Michael Table the number of respondents was determined to be 84 respondents. Data collection was carried out using questionnaire instruments in the form of Work Stress Scale and Mental Health Scale which have met the criteria for validity and reliability. The results showed that there was a non-significant positive relationship between work stress and mental health with a correlation value of 0.204 and significance of 0.136, as well as an influence contribution of 2.7%. The findings provide an idea that work stress is not the main factor in changes in mental health conditions, because most employees have quite good adaptability and self-regulation in dealing with work pressure. This research emphasizes the importance of organizations continuing to pay attention to other factors that are more dominant in maintaining employees' mental health to support the sustainability and effectiveness of company performance